Biological activities of protein-bound polysaccharides produced by Pleurotus ostreatus cultures with sunflower wastes - Salvador, C (2013)
Several species of mushrooms, as Pleurotus ostreatus, have been valued as edible and medicinal resources. These mushrooms may be an important source of compounds polysaccharides with medicinal properties as antioxidant, antitumoral, antimicrobial and immunological properties. The aim of this work was to produce and to evaluate the biological properties of proteinbound polysaccharides complexes, extra e intracellular (E‐PPS and I‐PPS), extracted from P.ostreatus cultures, using sunflower wastes as carbon source. Results showed that oral administration of EPPS extracts seems to indicate reduction of liver damage induced by ethanol‐administration, presenting a hepatoprotective activity equivalent to that observed for the standard drug, silymarin.